Characterization of poly(ADP-ribose)polymerase from Crithidia fasciculata: Enzyme inhibition by β-lapachone - Fernandez Villamil, Silvia Hebe (2001)
Crithidia fasciculata poly(ADP-ribose)polymerase (PARP) has been isolated and partially purified. This is the first PARP isolated from trypanosomatids; it requires DNA and histone for activity, using NAD+ as substrate. Thiol compounds specially dithiothreitol essentially contributed to PARP stability during purification and to PARP activity during assays. Nicotinamide, 3-aminobenzamide, theophylline, histamine, histidine, N-ethylmaleimide, p-chloromercuribenzoic acid, p-chloromercuriphenylsulfonic acid and o-iodosobenzoate inhibited PARP, thus confirming enzyme identity. PARP was also inhibited by the Fe(II)/H2O2 Fenton system. β-Lapachone inhibited PARP, apparently by direct interaction with the enzyme.